PENGGUNAAN MODEL PEMBELAJARAN INQUIRI TERBIMBING TERHADAP HASIL BELAJAR SISWA PADA KONSEP SISTEM EKSKRESI PADA MANUSIA DI SMP NEGERI 2 KOTA BANDA ACEH - Nulena Andalia; Armi Armi; Nurul Akmal; Muhammad Ridhwan (Bioilmi: Jurnal Pendidikan, 2019)
This study aims to find out the use of the Guided Inquiry learning model in improving student learning outcomes on the concept of excretion systems in humans in Banda Aceh City 2 Middle School. Data processing method is done by validity test, reliability test, normality test, homogeneity test and followed by t-test. The results of the study show that there is a difference between the application of a guided inquiry model and conventional methods towards student learning outcomes in the concept of excretion systems in humans. The acquisition of the difference value (gain) in the experimental class is 14.24 with an N-gain value of 0.44 and the control class is 5.42 with an N-gain value of 0.27. The results of the t-test obtained by the value of tcount of 2.14 and t table 1.68023 so that t-count> t-table. the average activity of students during learning has been done well, where activities carried out by students in the category of less (7.14%), good category (57.14%) and in the category is very good (35.72%). So the results of this study can be concluded that the application of the guided inquiry learning model influences the improvement of student learning outcomes in the concept of excretion systems in humans in class VIII of SMP Negeri 2 Kota Banda Aceh.